A novel mixing device for the reproducible generation of nonviral gene therapy formulations. - Davies, L; Nunez-Alonso, G; Hebel, H; Scheule, R; Cheng, S; Hyde, S; Gill, DR (2010)
Nonviral gene therapy utilizing plasmid DNA (pDNA) complexed with cationic lipids (lipoplexes) or cationic polymers (polyplexes) has demonstrated considerable potential for the treatment of a variety of diseases. However, progress toward clinical application is often delayed by the lack of reliable and scalable mixing of components sufficient to guarantee consistent performance in vivo. Attempts to improve and standardize mixing have been limited by the sensitivity of pDNA to shear-related degradation. Here we describe a simple pneumatic mixing device that enables the rapid and reproducible production of large volumes of nonviral gene therapy formulations and demonstrate its suitability for use with shear-sensitive pDNA.